THE BANKING SECTOR’S ASSETS IN ROMANIA. DEVELOPMENTS OVER THE PAST DECADE AND MID-RUN PROSPECTS - Andrei RĂDULESCU (Financial Studies)
The total assets of the banking sector in Romania increased significantly over the past decade, from RON 364.1 billion at the end of 2014 to RON 881.7 billion at the end of 2024, according to the statistics of the National Bank of Romania (NBR). This evolution was supported by several factors, including Romania's economic convergence towards the EU average. However, Romania continues to be a country with a very low banking assets-to-GDP ratio, below 50%. In this paper, we employ standard econometric tools and utilise quarterly data from NBR, Eurostat, and the Shillerdata platform to assess the evolution of the banking sector’s assets in Romania over the past decade. The main result of our analysis shows that the increase in banking assets was more dependent on the financing needs of the Government than on the evolution of the nominal GDP in Romania. This, in turn, represents a risk factor for the evolution of economic activity, for the macroeconomic stability and for the monetary policy transmission at the moment of the outbreak of the following shocks.